Incidence and predictors of oral feeding intolerance in acute pancreatitis: A systematic review, meta-analysis, and meta-regression - Bevan, Melody G.; Asrani, Varsha M.; Bharmal, Sakina; Wu, Landy M.; Windsor, John A.; Petrov, Maxim S. (Clinical nutrition (Edinburgh, Scotland), 2017)
Tolerance of oral food is an important criterion for hospital discharge in patients with acute pancreatitis. Patients who develop oral feeding intolerance have prolonged hospitalisation, use additional healthcare resources, and have impaired quality of life. This study aimed to quantify the incidence of oral feeding intolerance, the effect of confounders, and determine the best predictors of oral feeding intolerance. Clinical studies indexed in three electronic databases (EMBASE, MEDLINE, and the Cochrane Central Register of Controlled Trials) were reviewed. Incidence and predictor data were meta-analysed and possible confounders were investigated by meta-regression analysis. A total of 22 studies with 2024 patients met the inclusion criteria, 17 of which (with 1550 patients) were suitable for meta-analysis. The incidence of oral feeding intolerance was 16.3%, and was not affected by WHO region, age, sex, or aetiology of acute pancreatitis. Nine of the 22 studies investigated a total of 62 different predictors of oral feeding intolerance. Serum lipase level prior to refeeding, pleural effusions, (peri)pancreatic collections, Ranson score, and Balthazar score were found to be statistically significant in meta-analyses. Oral feeding intolerance affects approximately 1 in 6 patients with acute pancreatitis. Serum lipase levels of more than 2.5 times the upper limit of normal prior to refeeding is a potentially useful threshold to identify patients at high risk of developing oral feeding intolerance.